2023
DOI: 10.1021/acs.jctc.3c00341
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Charge-Flow Polarization Models

Abstract: We show that several models where electric polarization in molecular systems is modeled by charge-flow between atoms can all be considered as different manifestations of a general underlying mathematical structure. The models can be classified according to whether they employ atomic or bond parameters and whether they employ atom/bond hardness or softness. We show that an ab initio calculated charge response kernel can be considered as the inverse screened Coulombic matrix projected onto the zero-charge subspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 168 publications
0
1
0
Order By: Relevance
“…Production-type polarizable force fields use the fluctuating charge model at rank-0 and either the induced dipole or Drude oscillator model at the rank-1 level, some employ a combination of rank-0 and rank-1 polarization, and a few also include quadrupole polarization. , The fluctuating charge model has nonphysical properties, such as nonlinear scaling of the polarizability with system size and charge transfer over infinite distance, but alternative charge flow models without these artifacts have received much less attention . We have shown that all charge flow polarization models can be cast into a common mathematical framework, but they differ in terms of their parametrization and numerical implementation …”
Section: Introductionmentioning
confidence: 99%
“…Production-type polarizable force fields use the fluctuating charge model at rank-0 and either the induced dipole or Drude oscillator model at the rank-1 level, some employ a combination of rank-0 and rank-1 polarization, and a few also include quadrupole polarization. , The fluctuating charge model has nonphysical properties, such as nonlinear scaling of the polarizability with system size and charge transfer over infinite distance, but alternative charge flow models without these artifacts have received much less attention . We have shown that all charge flow polarization models can be cast into a common mathematical framework, but they differ in terms of their parametrization and numerical implementation …”
Section: Introductionmentioning
confidence: 99%